Laophontodes typicus T. Scott (Copepoda, Harpacticoida, Laophontodinae) – discovering a species complex by morphology - George, Kai Horst (European Journal of Taxonomy, 2018)
It appeared necessary to undertake a redescription of Laophontodes typicus T. Scott, 1894, but with the absence of the type specimen, several additional individuals collected from a number of regions were studied. The specimens chosen were from the western coast of Sussex and the Scottish Firth of Forth (UK), the Skjerstad fjord (Norway), the Patagonian continental slope (Chile) and the Great Meteor Seamount (subtropical north-eastern Atlantic Ocean). All specimens examined had been previously determined as L. typicus and deposited in the collections of renowned research institutions. However, detailed morphological comparison revealed that only the Sussex material can be assigned to L. typicus; the remaining specimens represent distinct species whose original assignment to L. typicus was erroneous, due to a morphological ambiguity. Thus, the current status of L. typicus must be regarded as a species complex. The Sussex material enabled a detailed redescription of L. typicus. Additionally, five new species are described, namely L. scottorum sp. nov., L. sarsi sp. nov., L. gertraudae sp. nov., L. monsmaris sp. nov. and L. norvegicus sp. nov. They exhibit some morphological similarity, but equally present discrete characters justifying their establishment as distinct taxa. The descriptions are accompanied by a detailed discussion that explains the justification of the splitting of L. typicus.